The Role of Ca2+ and BK Channels of Locus Coeruleus (LC) Neurons as a Brake to the CO2 Chemosensitivity Response of Rats - Imber, Ann N.; Patrone, Luis G.A. [UNESP]; Li, Ke-Yong; Gargaglioni, Luciane H. [UNESP]; Putnam, Robert W. (Elsevier, 2018)
The cellular mechanisms by which LC neurons respond to hypercapnia are usually attributed to an “accelerator” whereby hypercapnic acidosis causes an inhibition of K+ channels or activation of Na+ and Ca+2 channels to depolarize CO2-sensitive neurons. Nevertheless, it is still unknown if this “accelerator” mechanism could be controlled by a brake phenomenon. Whole-cell patch clamping, fluorescence imaging microscopy and plethysmography were used to study the chemosensitive response of the LC neurons. Hypercapnic acidosis activates L-type Ca2+ channels and large conductance Ca-activated K+ (BK) channels, which function as a “brake” on the chemosensitive response of LC neurons. Our findings indicate that both Ca2+ and BK currents develop over the first 2 weeks of postnatal life in rat LC slices and that this brake pathway may cause the developmental decrease in the chemosensitive firing rate response of LC neurons to hypercapnic acidosis. Inhibition of this brake by paxilline (BK channel inhibitor) returns the magnitude of the chemosensitive firing rate response from LC neurons in rats older than P10 to high values similar to those in LC neurons from younger rats. Inhibition of BK channels in LC neurons by bilateral injections of paxilline into the LC results in a significant increase in the hypercapnic ventilatory response of adult rats. Our findings indicate that a BK channel-based braking system helps to determine the chemosensitive respiratory drive of LC neurons and contributes to the hypercapnic ventilatory response. Perhaps, abnormalities of this braking system could result in hypercapnia-induced respiratory disorders and panic responses.
Keywords: central control of breathing; development; neuronal acid sensing; panic disorder; paxilline